CCL21 mediated dendritic cell migration: the role of self-generated chemokine gradients and Lfc - Inkilä, Sanni (My University, 2025)
Dendritic cells (DCs) link innate and adaptive immune systems together by presenting antigens and activating T cells in lymph nodes. Antigen encounter leads to DC maturation and expression of CCR7, a receptor for chemokines CCL19 and CCL21. Chemokine gradients guide DC migration to lymph nodes, but how these gradients form remains unclear. Previous studies show that DCs self-generate CCL19 gradients in uniform conditions, in a process dependent of Rho GEF protein Lfc. This study explores if DCs can self-generate CCL21 gradients and whether Lfc has a role in this process. To investigate DC migration, DCs were differentiated from Hoxb8-precursor cells, LPS-activated and characterized. Migration was analysed in 2D under agarose and in 3D collagen I gel and Matrigel. Tracking was performed using TrackMate (Fiji). To investigate Lfc’s role in CCL21 endocytosis and CCL21-mediated migration, Lfc WT and knockout DCs were compared in collagen I gel. CCL21 endocytosis was quantified from confocal images. Based on the results, DCs generate CCL21 gradients in all used settings, but not as efficiently under agarose as in the others, suggesting that matrix properties influence gradient formation. Lfc WT cells showed higher CCL21 endocytosis than KO cells. Surprisingly, there was no clear difference in migration between WT and KO cells. In conclusion, these findings suggest that DCs can self-generate CCL21 gradients, but Lfc is not essential for this process, unlike with CCL19. However, Lfc endocytosis assays indicate that Lfc has role in CCL21 endocytosis. This implies CCL21 gradient formation may occur via a different, endocytosis-independent mechanism, highlighting the need for further investigation.
Keywords: Dendritic cells, CCL21, migration, Lfc